High-performance training for sports - Joyce, David 1976-; Lewindon, Daniel (Human Kinetics, 2014)
A comprehensive sports training manual that is suitable for dedicated strength and conditioning practitioners and athletes and coaches looking to expand their knowledge on how to develop and optimise human performance and athletic capacity. Each topic is addressed by a world renowned expert in a specific component of sports conditioning